Dari Rasionalitas Weberian ke Birokrasi Adaptif: Evolusi Paradigma Administrasi Modern - Sri Yulianty Mozin; Alexander H. Badjuka; Yasifah Tri Andini; Riskawati Fitra; Sri Rahayu Nadia (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
This article traces the evolution of modern public administration from Weberian rational bureaucracy to contemporary ideas of adaptive bureaucracy. We synthesize four classic books and eleven peer‑reviewed journal articles to map paradigm shifts from traditional bureaucracy to New Public Management (NPM), New Public Governance (NPG), digital‑era governance, complexity leadership, collaborative governance, and organizational resilience. Using an integrative literature review, we (1) compare core design logics (structure, coordination, decision rights, and accountability) across paradigms; (2) distill a five‑pillar conceptual model of adaptive bureaucracy—ambidextrous structure, agile learning processes, networked/collaborative governance, data‑driven/digital capabilities, and resilience/risk governance; and (3) advance actionable propositions for reform. We argue that adaptive bureaucracy reconciles rule‑bound reliability with continuous adaptation by coupling Weberian legality and due process with exploration, co‑creation, and digital enablement. The model clarifies how public organizations can meet volatility and complexity without sacrificing legitimacy. Implications include redesigning roles and incentives for exploration–exploitation balance, codifying agile yet auditable routines, scaling collaborative platforms, and investing in socio‑technical data infrastructure and resilience exercises. The article contributes a structured bridge between classic administrative rationality and contemporary adaptive governance suitable for volatile, uncertain, complex, and ambiguous (VUCA) contexts.